On the Cutting Edge: Movements and Institutional Examples of Technological Disruption. Issue 173 (1st March 2016) - Leon, Marjorie Roth; Price, Todd Alan
Abstract : This chapter describes technological disruptions in higher education that pose challenges and offer opportunities to college and university students, faculty, and administrators. It provides examples of innovative responses being explored by 2‐year and 4‐year higher education institutions.